Evaluation of nursing students' health fatalism, knowledge, and attitudes toward patients with epilepsy - Turan, Gulcan Bahcecioglu; Dayapoglu, Nuray; Ozer, Zulfunaz (Academic Press Inc Elsevier Science, 2022)
Aim: This study was conducted to determine the relationship between nursing students' health fatalism, epilepsy knowledge, attitudes, and some sociodemographic variables. Methods: The descriptive cross-sectional study was conducted with 423 nursing department students who were studying at a state university and who agreed to participate in the study in the Elazig province in eastern Turkey during the 2020-2021 academic year. The data were collected using a Sociodemographic Information Form, the Health Fatalism Scale (HFS), the Epilepsy Knowledge Scale (EKS), and the Epilepsy Attitude Scale (EAS). Results: The nursing students had total mean scores of 46.95 +/- 12.98, 6.94 +/- 3.81, and 50.19 +/- 8.47 for the HFS, EKS, and EAS, respectively. A positive and significant correlation was found between the EKS and EAS scores. First-year students had lower HFS scores than students in their second and fourth years. Third and fourth-year students, those living in rural areas, and those who had patients with epilepsy in their families or immediate environments had higher EKS scores. Female students and those who had patients with epilepsy in their families or immediate environments had higher EKS and EAS scores. A significant positive correlation was found between age and the EKS score, whereas a significant negative correlation was found between age and the EAS score. Conclusion: While nursing students generally had low levels of epilepsy knowledge, they had positive attitudes toward epilepsy and moderate levels of health fatalism. The study found that students' positive attitudes toward epilepsy increased as their levels of knowledge about the disorder increased. Age, gender, educational status, place of residence, the presence of a chronic disease, and knowing someone with epilepsy all affected HFS, EKS, and EAS scores. (c) 2021 Published by Elsevier Inc.
Keywords: Health fatalism; Epilepsy knowledge and attitudes; Nursing student